2016
DOI: 10.1080/21623945.2016.1220452
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signaling regulating adipose stromal cell trafficking

Abstract: Adipocyte progenitors, known as adipose stromal cells (ASC), can become mobilized, recruited by tumors, and contribute to cancer progression. Mechanisms underlying ASC trafficking have remained obscure. We recently reported that CXCL1 expressed by cancer cells chemoattracts ASC expressing CXCR1 in obesity. As a candidate mechanism of CXCL1 activation, we identified interleukin (IL)-22, systemic circulation of which is increased in obesity. It has been reported that IL-22 signaling through IL-22R is upstream of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Adipose stromal cells (ASCs), which are adipocyte progenitors within fatty tissue, have been implicated in the development of these cancers (7,8). While released factors from abdominal fat can be transported systemically, identification of circulating ASCs in obese subjects and recruitment of these cells by tumor-produced chemokines suggest that ASCs are trafficked to target tissue sites and embedded within the tumor microenvironment (9–12).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose stromal cells (ASCs), which are adipocyte progenitors within fatty tissue, have been implicated in the development of these cancers (7,8). While released factors from abdominal fat can be transported systemically, identification of circulating ASCs in obese subjects and recruitment of these cells by tumor-produced chemokines suggest that ASCs are trafficked to target tissue sites and embedded within the tumor microenvironment (9–12).…”
Section: Introductionmentioning
confidence: 99%
“…ASCs derived from adipose tissues, including the parametrial fat near the uterus, can be mobilized via chemokine actions to the endometrial microenvironment and promote epithelial tumorigenesis ( Ma et al, 2016 ; Zhang et al, 2010 ; Zhang and Kolonin, 2016 ). These adipocyte progenitors exert paracrine actions by secreting abundant PAI-1 and other factors that may alter signaling responses in nearby EECs.…”
Section: Discussionmentioning
confidence: 99%
“…The poor survival of obese patients with prostate cancer has been linked to ASC trafficking from WAT to tumors, which is mediated by CXCL1 that is secreted from malignant epithelium and signaling on ASC via its receptor CXCR1 [138]. It was also found that the secretion of CXCL1 by tumors in the setting of obesity is induced by WAT leukocyte-derived interleukin IL-22 signaling through IL-22R on cancer cells [152].…”
Section: Adipose Cell Engagement In Cancermentioning
confidence: 99%